Comparative efficacy of commercial Chinese polyherbal preparation for coronary microvascular dysfunction: a systematic review and network meta-analysis of randomized controlled trials - Wang, Wujiao; Zhang, Jun; Wang, Xinyue; Li, Yuxuan; Li, Yudou; Pu, Fenglan; Yang, Zhifei; Wan, Jie; Zhu, Haiyan; Li, Tianli; Chang, Peifen (Frontiers in Pharmacology, 2025)
BackgroundCommercial Chinese polyherbal preparations (CCPPs) are widely used in China to treat coronary microvascular dysfunction (CMD). However, the discussion on the best CCPPs continues. This network meta-analysis (NMA) aimed to evaluate and rank the relative efficacy of CCPPs for CMD and summarize the possible mechanisms according to experimental researches.MethodFrom the time the database was established to 12 December 2024, We systematically searched eight databases and two registry systems, including Web of Science, Cochrane Library, PubMed, Embase, China National Knowledge Infrastructure (CNKI), Wanfang database, China Science and Technology Journal Database (VIP), Chinese Biomedical Literature database (CBM), Clinical Trials, and the China Clinical Trials Registry. Clinical randomized controlled trials (RCTs) of nine CCPPs in treating CMD, including Shexiangbaoxin Pill (SXBX), Tongxinluo Capsule (TXL), Shexiangtongxindi Pill (SXTXD), Yindanxinnaotong Capsule (YDXNT), Kedalin Tablet (KDL), Xinbao Pill (XB), Xinkeshu Tablet (XKS), Diaoxinxuekang Capsule (DAXXK), and Yixintongluo Capsule (YXTL), were retrieved. The primary outcomes were the Index of Microcirculatory Resistance (IMR) and Coronary Flow Reserve (CFR). Secondary outcomes included the Angina attack frequency, hypersensitive C-reactive protein (hs-CRP), Endothelin-1 (ET-1), Nitric oxide (NO), and Low-density lipoprotein cholesterol (LDL-C). Two researchers performed rigorous data extraction and quality assessment. The quality of the included RCTs was evaluated using the Cochrane Risk of Bias assessment tool, version 2.0 (RoB 2). We then conducted the NMA using a random-effects model under the frequentist framework with Stata version 15. Interventions were ranked based on the surface under the cumulative ranking curve (SUCRA) probability values. The risk of bias was detected using funnel plots and Egger’s test.ResultA total of 39 RCTs involving 3,240 patients were included in this study. NMA results showed that SXBX had the highest probability of being the best treatment on account of the reduction of IMR [MD = −5.93, 95% CI (−8.75, −3.11)] and LDL-C [[MD = −0.56, 95% CI (−0.99, −0.14)], XB showed better efficacy in improving CFR [MD = 0.71, 95% CI (0.53, 0.89)], TXL showed better efficacy in angina attack frequency [MD = −5.30, 95% CI (−7.08, −3.53)]; YXTL showed better efficacy in hs-CRP [MD = −5.04, 95% CI (−8.38, −1.7)]; XKS showed better efficacy in ET-1 [MD = −43.3, 95% CI (−59.71, −26.89)]; YDXNT showed better efficacy in NO [MD = 17.69, 95% CI (6.07, 29.32)]. In addition, the protective effect of CCPP on CMD may be achieved by altering multiple signalling pathways through anti-atherosclerosis, anti-vascular smooth muscle cell proliferation and migration, anti-inflammation, antioxidant stress, protection of vascular endothelium, improving energy metabolism, antiplatelet activation and aggregation, and promoting angiogenesis.ConclusionCCPPs combined with conventional therapy led to a significant improvement in CFR and NO, as well as a reduction in IMR, angina attack frequency, hs-CRP, ET-1, and LDL-C levels. SXBX emerged as the optimal treatment regimen for lowering IMR and LDL-C levels. Additionally, XB demonstrated superiority in improving CFR. TXL demonstrated superiority in reducing angina attack frequency, YXTL in lowering hs-CRP levels, XKS in lowering ET-1 levels, and YDXNT in increasing NO levels. Nevertheless, the majority of the evidence was rated as low certainty according to the GRADE assessment. Conclusion should be framed as hypothesis-generating rather than definitive, and there is a need for large-scale, multicenter, and direct comparative RCTs of CCPPs treated for CMD to generate higher-quality evidence.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42025632143.